2014
DOI: 10.1021/cg401817g
|View full text |Cite
|
Sign up to set email alerts
|

Metallacarborane-Based Metal–Organic Framework with a Complex Topology

Abstract: The long, linear cobalt(III) bis(dicarbollide)based bis(isophthalic acid) anion was synthesized as a tetraphenylphosphonium salt in five steps from 8-iodo-closo-1,2-C 2 B 10 H 11. The solvothermal reaction between the anionic bis(isophthalic acid) linker and copper(II) nitrate in acidified DMF yielded single crystals. Despite the tendency for copper(II) and analogous linear tetraacids to form members of an isoreticular family of metal−organic frameworks (MOFs) with the fof topology, single-crystal X-ray diffra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…The angles involving atom O2 (located at the apical position) and the equatorial plane (Table 2) confirm an approximately square-pyramidal coordination geometry. This coordination geometry of the five-coordinated Cu II cation has been reported previously in recent years (Kennedy et al, 2014;Tjioe et al, 2011;Boonmak et al, 2009;Cui et al, 2008).…”
Section: Resultssupporting
confidence: 85%
“…The angles involving atom O2 (located at the apical position) and the equatorial plane (Table 2) confirm an approximately square-pyramidal coordination geometry. This coordination geometry of the five-coordinated Cu II cation has been reported previously in recent years (Kennedy et al, 2014;Tjioe et al, 2011;Boonmak et al, 2009;Cui et al, 2008).…”
Section: Resultssupporting
confidence: 85%
“…Cobalt-containing p-carboranyl MOFs of the formula [Co 4 (OH) 2 (O 2 C-CB 10 H 10 C-CO 2 ) 3 (DMF) 2 ] n employing a variety of solvents have been prepared, all of which crystallize as 3D networks with large open channels between the carborane cages and efficiently separate CO 2 -CH 4 , CO 2 -N 2 , and O 2 -N 2 mixtures. 145 In this work, the remarkable isolation and characterization of materials with three different topologies prepared with the same components under the same conditions illustrates the fact that even carefully designed syntheses can lead to unexpected results. 143 Another variety, obtained when an excess of dabco was used, has the composition [Ag 2 (dabco) 3 (CH 3 CN) 2 ] 2 ·[Co(C 2 B 9 H 11 ) 2 ] in a 3D network.…”
Section: View Article Onlinementioning
confidence: 76%
“…[1][2][3][4][5] Among the various derivatives of carboranes, special attention is paid to p-complexes of transition metals with carborane ligands, called metallacarboranes. The most known of them, cobalt bis(dicarbollide) [3,3 0 -Co(1,2-C 2 B 9 H 11 ) 2 ] À attracts increasing interest from researchers working in various elds from medical chemistry to [6][7][8][9][10][11] materials science [12][13][14][15][16][17][18] to due to its extraordinary high stability, low toxicity 19 and almost unlimited possibilities for chemical modication. 20,21 Recently, we suggested that cobalt bis(dicarbollide) can be used as a structural element in the design of molecular switches.…”
Section: Introductionmentioning
confidence: 99%